1997
DOI: 10.1086/516210
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of an Unusual Anaerobic Pigmented Gram‐Negative Rod Isolated from Normal and Inflamed Appendices

Abstract: During our studies of the bacterial etiology of appendicitis, we often isolated a previously undescribed anaerobic gram-negative rod. This organism resembled the Bacteroides fragilis group because it was resistant to bile and because of its special-potency-disk pattern (resistant to vancomycin, kanamycin, and colistin), but unlike the B. fragilis group, this bacterium produced brown pigment on media containing hemolysed blood. The cellular fatty acid pattern, with iso-C15:0 being the predominant acid, was most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Finally, several taxa of the genus Alistipes were associated with the phenotype of frequently recurrent abdominal pain. One example from this genus, Alistipes putredinis , resembles members of the Bacteroides fragilis group 35, 36 , and is considered to be a commonly found gut commensal microbe of the Bacteroidetes phylum 37 . This species has been isolated from inflamed and non-inflamed intestinal tissues in studies of the bacteriology of appendicitis in children 35,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several taxa of the genus Alistipes were associated with the phenotype of frequently recurrent abdominal pain. One example from this genus, Alistipes putredinis , resembles members of the Bacteroides fragilis group 35, 36 , and is considered to be a commonly found gut commensal microbe of the Bacteroidetes phylum 37 . This species has been isolated from inflamed and non-inflamed intestinal tissues in studies of the bacteriology of appendicitis in children 35,38 .…”
Section: Discussionmentioning
confidence: 99%
“…This strain is one of several strains with similar properties [3] that were isolated mainly from pediatric patients with inflamed, gangrenous or non-inflamed appendices [4,5]. Though the type strain AHN2437 T resembled members of the Bacteroides fragilis group in bile-resistance and positive indole reaction, it was found, together with the type strain of Bacteroides putredinis, to form a separate phylogenetic lineage apart from authentic Bacteroides species [1].…”
Section: Introductionmentioning
confidence: 99%
“…With routine tests, this organism resembled members of the Bacteroides fragilis group; however, the cellular fatty acid composition dominated by iso -C15:0 and production of brown pigment on media containing hemolyzed blood suggested that the organism was most closely related to the genus Porphyromonas ( 1 ). However, 16S rDNA sequence comparison showed highest sequence relatedness with B. putredinis, and the reclassification of B. putredinis in a novel genus, Alistipes , and the classification of the novel bacterium as A. finegoldii were proposed ( 4 ).…”
mentioning
confidence: 97%
“…To the Editor: Alistipes finegoldii was previously isolated from appendiceal tissue samples in children with acute appendicitis and from perirectal and brain abscess material ( 1 , 2 ). 16S rDNA sequencing studies showed that this bacterium clustered with A. putredinis (Figure) in the Bacteroidetes group ( 4 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation